Application of Central Difference Scheme to the solution of natural convection equations for irregular shaped enclosures - Varol, Yasin; Koca, Ahmet; Öztop, Hakan Fehmi (Asian Network for Scientific Information, 2007)
The present study deals with the numerical solution of laminar natural convection equations for irregular shaped enclosure using Central Difference Scheme (CDS). Governing equations in streamfunction-vorticity form were discretized over a grid arrangement. A code was developed using an algorithm. Successive Under Relaxation (SUR) method was used to solve algebraic equations. Two different geometries were chosen as illustrative examples such as triangular and irregular shaped enclosures whose bottom wall was isothermally cooled and inclined walls were isothermally heated. The obtained results were compared with different techniques which are available from the literature. The obtained results show good agreement between literature and the present data. © 2007 Asian Network for Scientific Information.
Keywords: Central difference; Computational modeling; Irregular shape; Natural convection